Evaluasi Penerapan Manajemen Pendidikan Berbasis Budaya Mutu di SD Negeri Banjarpanji Kabupaten Sidoarjo - Rahman, Muhammad Afifi (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Research related to education management based on quality and excellence has not been widely carried out so far. So far, research that is model development has only developed a learning model. evaluation of education management based on quality and excellence we view as very important for the development of education management. In connection with this fact, this evaluation research is deliberately focused on implementation evaluation, especially in terms of the implementation process and its impact on school management. therefore in this case will conduct a study on evaluating the implementation of quality culture-based education management at Banjarpanji State Elementary School, Tanggulangin District, Sidoarjo Regency and focusing on developing quality and excellence and maintaining quality in efforts to manage education at Banjarpanji State Elementary School, Tanggulangin District , Sidoarjo Regency, therefore In this study, we conducted an evaluation of quality and excellence-based education management at the Bajarpanji Public Elementary School, Tanggulangin District, Sidoarjo Regency, and have also prepared an education management plan based on quality and excellence based on the values ​​and spirit that developed